Collision metastasis in a pelvic lymph node from urothelial and prostatic carcinoma: a rare case report and literature review - Shi, Xue-Dong; Shen, Qiong-Nan; Wei, Li; Chen, Li-Juan; Wang, Hui-Fen; Zheng, Xu-Dong; Ma, Qi (Frontiers in Oncology, 2025)
Metastasis of both urothelial carcinoma and prostatic carcinoma to the same lymph node is extremely rare. We report a case of collision metastasis involving bladder urothelial carcinoma and prostatic adenocarcinoma in a 76-year-old male. The patient underwent laparoscopic radical cystoprostatectomy and bilateral pelvic lymph node dissection. Final pathological examination revealed high-grade urothelial carcinoma (pT2bN1M0) and prostatic adenocarcinoma (pT2N1M0, Gleason score 4 + 4 = 8). Notably, coexisting metastatic foci of urothelial carcinoma and prostatic adenocarcinoma were identified within a single pelvic lymph node. During the 18-month postoperative follow-up, the patient developed multifocal hepatic and bone metastases. Collision metastasis is a rare clinical event with complex prognostic implications. This study aims to enhance understanding of this unique pathological entity and provide clinical references for the management of such cases through case analysis and literature review.